Desarrollo de un sistema biometrico de control de acceso de entrada y salida vehicular - Buenaño, G. (2009)
Any access control system aims to allow entry of personnel authorized to specific sites. Access systems based on licenses authorize pieces of plastic, but cannot distinguish who carries the carnet. Systems that use personal identification numbers only require that an individual knows a specific number to grant access. Biometric devices verified the identity of a person through physical characteristics unique and unchanging as the dimensions of the hand, peculiarities or measures of the eyes, fingerprints or voice. This document aims to implement a control security in what refers to access vehicle to the parking garages of the Espol by an isolated or standalone device consisting of a biometric reader and a driver door full for a single door. Acceptance of the user will always be an essential factor in the successful implementation of a biometric device. We present the financial analysis of the marketing of a biometric system along with their fingerprint reading devices with which companies or institutions concerned can examine this economic proposal, its benefits and new business opportunities.